Pengaruh Penambahan Abu Ijuk Pada Beton Normal - Ika Tangma'ti; Frans Phengkarsa; Lisa Febriani (Paulus Civil Engineering Journal, 2023)
Concrete is one of the most commonly used building materials in the industrial sector. This is what encourages the use of palm fiber ash as an added ingredient in concrete. Palm fiber which is underutilized and left alone gives rise to a new idea, namely to use the palm fiber as an added ingredient in concrete. The American Concrete Institute (ACI) method was used to prepare the sample. The test is carried out when the concrete has passed the holding time of 7, 21 and 28 days.. The purpose of this study was to determine the effect of adding 3%, 6% and 9% palm fiber ash on compressive strength, split tensile strength and modulus of elasticity. In this research, the concrete quality is planned to be 50 MPa. From the test results, it was obtained that the concrete compressive strength values ​​for the percentage variations of 0%, 3%, 6% and 9% were respectively 26.893 MPa, 26.799 MPa, 21.892 MPa and 19.061 MPa, split tensile strength test for percentage variations of 0%, 3 %, 6%, and 9% respectively 2.453 MPa, 2.430 MPa, 2.170 MPa and 1.887 MPa, and testing the modulus of elasticity for the percentage variation of 0%, 3%, 6% and 9% respectively 22209, 358 MPa, 21064.331 MPa, 19496.646 MPa and 18971.406 MPa. From the proceeds of the study it can be concluded that the use of the addition of palm fiber ash as an added ingredient decreased with increasing variations in the percentage of palm ashes.